A mixed iron–manganese based pyrophosphate cathode, Na2Fe0.5Mn0.5P2O7, for rechargeable sodium ion batteries. Issue 5 (14th January 2016) - Shakoor, Rana A.; Park, Chan Sun; Raja, Arsalan A.; Shin, Jaeho; Kahraman, Ramazan
Abstract : The development of secondary batteries based on abundant and cheap elements is vital. Abstract : The development of secondary batteries based on abundant and cheap elements is vital. Among various alternatives to conventional lithium-ion batteries, sodium-ion batteries (SIBs) are promising due to the abundant resources and low cost of sodium. While there are many challenges associated with the SIB system, cathode is an important factor in determining the electrochemical performance of this battery system. Accordingly, ongoing research in the field of SIBs is inclined towards the development of safe, cost effective cathode materials having improved performance. In particular, pyrophosphate cathodes have recently demonstrated decent electrochemical performance and thermal stability. Herein, we report the synthesis, electrochemical properties, and thermal behavior of a novel Na2 Fe0.5 Mn0.5 P2 O7 cathode for SIBs. The material was synthesized through a solid state process. The structural analysis reveals that the mixed substitution of manganese and iron has resulted in a triclinic crystal structure ( P 1̄ space group). Galvanostatic charge/discharge measurements indicate that Na2 Fe0.5 Mn0.5 P2 O7 is electrochemically active with a reversible capacity of ∼80 mA h g −1 at a C/20 rate with an average redox potential of 3.2 V. ( vs. Na/Na + ). It is noticed that 84% of initial capacity is preserved over 90 cycles showing promising cyclability. It is also noticed that the rate capability of Na2 Fe0.5 Mn0.5 P2 O7 is better than Na2 MnP2 O7 . Ex situ and CV analyses indicate that Na2 Fe0.5 Mn0.5 P2 O7 undergoes a single phase reaction rather than a biphasic reaction due to different Na coordination environment and different Na site occupancy when compared to other pyrophosphate materials (Na2 FeP2 O7 and Na2 MnP2 O7 ). Thermogravimetric analysis (25–550 °C) confirms good thermal stability of Na2 Fe0.5 Mn0.5 P2 O7 with only 2% weight loss. Owing to promising electrochemical properties and decent thermal stability, Na2 Fe0.5 Mn0.5 P2 O7, can be an attractive cathode for SIBs.